Is the FIFA 11+ Warm-Up Effective for Inducing Acute Knee Adaptations in Recreational Soccer Players? - Patricia Caudet; Ernest Baiget; Abraham Batalla; Joshua Colomar; Miguel Crespo; Rafael Martínez-Gallego; Francisco Corbi (Journal of Functional Morphology and Kinesiology, 2025)
Objectives: Soccer is the most practiced sport around the world. The injury incidence has an estimated rate of up to 70 injuries per 1000 h of play. FIFA 11+ is a program designed to prevent injuries and optimize performance. The purpose of this study was to analyze the acute effects of this program as a warm-up on different functional, physiological, and mechanical properties of various knee tissues and whether there were differences between genders. Methods: The sample included 45 recreational soccer players. Several muscular and tendon mechanical properties, muscular oxygen saturation, electromyography, maximum voluntary contraction, and rate of force development were analyzed, before and after performing the FIFA 11+. Results: Only a moderate significant increase in muscle oxygen saturation in men from pre- to post-test was reported. No other parameters showed statistically significant differences between groups, suggesting that the intervention may lack clinical relevance. The reported effect sizes were mostly trivial, so differences are unlikely to have significant practical relevance. Statistical analyses were performed using a 2 × 2 factorial repeated measures factorial ANOVA with Bonferroni post hoc comparisons. Conclusions: FIFA 11+ warm-up does not provide a sufficient stimulus to elicit mechanical or metabolic responses in the per-knee structures. Other warm-up designs may be more appropriate for finding these effects.